The impact of social networking addiction on the academic achievement of university students globally: A meta-analysis - Nader Salari; Hosna Zarei; Shabnam Rasoulpoor; Hooman Ghasemi; Amin Hosseinian-Far; Masoud Mohammadi (Public Health in Practice)
Objective: There have been a significant surge in the adoption of social networks by different groups over the past decade and students are no exception. These networks create several opportunities for university students, yet they pose a number of threats. Excessive use of social networks can lead to addiction to these networks and can affect students’ academic performance. The aim of this study was to investigate the effect of social media addiction on academic performance of students around the world through a systematic review and meta-analysis. Study design: systematic review and meta-analysis. Methods: In this systematic review and meta-analysis, the keywords of Social Network, Addiction, Academic Performance, and University Students, and their suitable combinations were searched within PubMed, Web of science, JISC Library Hub Discover, the Library of congress, and the Google scholar search engine with no lower time limit and until February 2022. The identified sources were then transferred into the EndNote reference management software. Subsequently, duplicate studies were eliminated, and the remaining studies were evaluated in 3 stages (Screening, Eligibility Evaluation, and Quality Assessment). Heterogeneity of studies was assessed using the I2 index, analysis of eligible studies was completed be embracing the random effects model, and the data analysis was performed within the Comprehensive Meta-Analysis (v.2) software. Results: The correlation obtained from meta-analysis −0.172 (95 % CI: −0.320 - (-0.016)) showed that the negative impact of social network addiction on students' academic achievement. Conclusion: There is a negative relationship between social media addiction and students' academic performance. Therefore, it is necessary for students to be aware of the negative consequences of addiction to social networks and improve their academic performance by managing the time when using these networks.